Zakat and Tax as Instruments of Fiscal Justice: A Normative Analysis of Yusuf Al-Qardhawi's Thoughts - Nilasari Siagian; Surono Zamroni; Muhammad Fitrah Al Fayed Pane; Hizass Raihan Saragih; Dwi Raisyah Sirait (Al-Qalam Institute, 2025)
Zakat and taxation are two fiscal instruments that play a significant role in promoting social and economic justice. In contemporary Muslim societies, debates over the relationship between zakat and taxes have become increasingly important, particularly regarding their legal legitimacy and their roles in modern state financial systems. This study aims to analyse Yusuf al-Qardhawi’s thought on the concept, legal basis, and relationship between zakat and taxation from the perspective of Islamic law. The research employs a qualitative method with a library research design. Primary data were derived from Yusuf al-Qardhawi’s works; secondary data consisted of classical and contemporary fiqh literature, scholarly journal articles, and relevant regulations. Data were analysed using a content analysis approach. The findings reveal two main points. First, Qardhawi distinguishes zakat as a permanent religious obligation (tsābit) grounded in the Qur’an and Sunnah. At the same time, taxes are viewed as contextual state obligations (mutaghayyir) justified through public interest and the objectives of Islamic law. Second, Qardhawi proposes that zakat and taxes should not be understood as competing obligations but as complementary instruments that can operate synergistically to promote fiscal justice and public welfare. This study concludes that integrating zakat and taxation within a fiscal justice framework can strengthen public finance policies in contemporary Muslim countries by aligning religious values with modern governance and enhancing distributive justice.